Organization and managament of educational centers: a pending subject? - Gairín Sallán, Joaquín (Avances en Supervisión Educativa, 2020)
This contribution is based on the impact that the successive educational reforms carried out in Spain have had on the organizational and institutional management processes. Once both terms and their relationship with the politics and administration of education have been clarified, we analyze the reality of institutional autonomy as a starting point, and the conditioning factors affecting the process (institutional projects, school management and continuous improvement). We conclude that the levels of real autonomy have been decreasing and the conditioning factors affecting the process have been limited because of the previous reason and by the continued regulations changes and setbacks in their orientation. The organization is still a pending subject and the management is limited to the compliance with external regulations.
Keywords: education administration; educational management; management of educational centers; school autonomy; school project; school management; institutional self-assessment